The Role of Renal Vascular Reactivity in the Development of Renal Dysfunction in Compensated and Decompensated Congestive Heart Failure - Vojtech Kratky; Libor Kopkan; Sona Kikerlova; Zuzana Huskova; Milos Taborsky; Janusz Sadowski; Frantisek Kolar; Ludek Cervenka (Kidney & Blood Pressure Research, 2018)
Background/Aims: Reduction of renal blood flow (RBF) is commonly thought to be a causative factor of renal dysfunction in congestive heart failure (CHF), but the exact mechanism of the renal hypoperfusion is not clear. Apart from the activation of neurohormonal systems controlling intrarenal vascular tone, the cause might be altered reactivity of the renal vasculature to endogenous vasoactive agents. Methods: To evaluate the role of this mechanism, we assessed by an ultrasonic transient-time flow probe maximum RBF responses to renal artery infusion of angiotensin II (ANG II), norepinephrine (NE) and acetylcholine (Ach) in healthy male rats and animals with compensated and decompensated CHF. CHF was induced by volume overload achieved by the creation of the aorto-caval fistula (ACF) in Hannover Sprague-Dawley rats. Results: Maximum responses in RBF to ANG II were similar in rats studied five weeks (compensated phase) and 20 weeks (decompensated phase) after ACF creation when compared to sham-operated rats. On the other hand, NE elicited larger maximum decreases in RBF in rats with CHF (five and 20 weeks post-ACF) than in sham-operated controls. We observed greater maximum vasodilatory responses to Ach only in rats with a compensated stage of CHF (five weeks post-ACF). Conclusion: Greater renal vasoconstrictor responsiveness to ANG II or reduced renal vasodilatation in response to Ach do not play a decisive role in the development of renal dysfunction in ACF rats with compensated and decompensated CHF. On the other hand, exaggerated renal vascular responsiveness to NE may be here a contributing causative factor, active in either CHF phase.